EXPANSION OF STRATEGIC OPPORTUNITIES IN ECONOMIC COOPERATION BETWEEN TURKEY AND UKRAINE - Savchuk, Olena; Kryuchkovskyi, Viktor (Journal of European Economy, 2017)
Bilateral relations between Ukraine and Turkey are strategically important for both countries as a part of planned integration into the EU. It is feasible to adjust the trade structures before establishing free economic inodes. It is necessary that Ukraine insist on such a trade policy, which will ensure it does not become a raw material appendage for Turkey.